Liquid-Ordered Phase Formation by Mammalian and Yeast Sterols: A Common Feature With Organizational Differences - Khmelinskaia, Alena; Marquês, Joaquim M. T.; Bastos, André E. P.; Antunes, Catarina A. C.; Bento-Oliveira, Andreia; Scolari, Silvia; Lobo, Gerson M. da S.; Malhó, Rui; Herrmann, Andreas; Marinho, H. Susana; de Almeida, Rodrigo F. M. (Frontiers in Cell and Developmental Biology, 2020)
Here, biophysical properties of membranes enriched in three metabolically related sterols are analyzed both in vitro and in vivo. Unlike cholesterol and ergosterol, the common metabolic precursor zymosterol is unable to induce the formation of a liquid ordered (lo) phase in model lipid membranes and can easily accommodate in a gel phase. As a result, zymosterol has a marginal ability to modulate the passive membrane permeability of lipid vesicles with different compositions, contrary to cholesterol and ergosterol. Using fluorescence-lifetime imaging microscopy (FLIM) of an aminostyiryl dye in living mammalian and yeast cells we established a close parallel between sterol-dependent membrane biophysical properties in vivo and in vitro. This approach unraveled fundamental differences in yeast and mammalian plasma membrane organization. It is often accepted that in eukaryotes areas that are sterol-enriched are also rich in sphingolipids, constituting highly ordered membrane regions. Our results support that while cholesterol is able to interact with saturated lipids, ergosterol seems to interact preferentially with monounsaturated phosphatidylcholines. Taken together, we show that different eukaryotic kingdoms developed unique solutions for the formation of a sterol-rich plasma membrane, a common evolutionary trait that accounts for sterol structural diversity.